Contribution of integrating seismic coherency and AVO attributes in delineating sand bars reservoirs, Offshore Nile Delta, Egypt, A case study - Aia M. Dahroug; Sharafeldin M. Sharafeldin; Walid M. Mabrouk; Mahmoud H. Noaman (Egyptian Journal of Petroleum)
The geometry and extension of Offshore Nile Delta sand bar complex deposited in a structurally controlled shallow marine basin is delineated by integrating seismic coherency and AVO attributes. Coherency is the imaging of discontinuities within the seismic data, where faults, sand bar boundaries and fluid contacts (GWC) were mapped, using an optimum analysis window of 40 × 40 × 64, and instantaneous amplitude of time slice image map at 1652 ms. AVO attributes are applied to reservoir sands of significant bright spot response. AVO attributes volumes, include the (A * B), (A + B), and (A − B) of the intercept and gradient, generated from near, mid, and far angle stacks. The seismic coherency volume delineated two major bounding faults of the reservoir, that converged at the western end of the field and open out to the east where, the reservoir is dip-closed. Four boundaries between five sand bars oriented in NW-SE direction are detected. GWC is delineated at the deepest part of the reservoir towards the southeastern part.AVO attributes indicated that the reservoir top is characterized by positive bright spots, negative Poisson’s ratio, and increasing in the scaled S-reflectivity. Meanwhile, the bottom is characterized by bright spots, positive Poisson’s ratio, and decreasing in the scaled S-reflectivity. AVO volumes were consistent, and show the typical response of Class III gas sands. Five high positive amplitude sand bars oriented NW-SE are confirmed. Three of them were successfully tested. The two prolific southern sand bars exhibit higher amplitude haven’t been tested. Keywords: Offshore Nile Delta, Gas sand bar reservoir, Seismic coherency, AVO attributes